Pemberian Pupuk Silikat dan Pupuk Kandang Terhadap Pertumbuhan, Kadar Brix, dan Hasil Tanaman Sorgum (Sorghum bicolor (L.) Moench) - Dita Apliza; Mansur Ma’shum; Suwardji Suwardji; Verina Januati Wargadalam (Postgraduate, University of Mataram, 2020)
Abstract: Research on the application of silicate fertilizer and manure to growth, brix level, and yield of sorghum (Sorghum bicolor (L.) Moench) was investigated to find ways to increase sorghum productivity in the dry land. The research method used was an experimental method that was set in a randomized block design consisting of 9 treatments namely control (Si0P0), without silicate and manure, 5 tones/ha (Si0P5), without silicate and manure 10 tones/ha (Si0P10), silicate 100 kg/ha and without manure (Si100P0), silicate 100 kg/ha and manure 5 tones/ha (Si100P5), silicate 100 kg/ha and manure 10 tones/ha (Si100P10), silicate 200 kg/ha and without manure (Si200P0), silicate 200 kg/ha and manure 5 tones/ha (Si200P5), and silicate 200 kg/ha and manure 10 tones/ha (Si200P10). Each treatment was replicated 3 times and the size of the plot was 6x6 m2. The results indicated that the application of silicate fertilizer and manure could significantly increase yield and brix levels. Application of silicate fertilizer of 200 kg/ha and manure 5 tonnes/ha gave higher results for the production of sorghum was 6056 kg/ha. However, the growth of sorghum was not affected significantly to the growth of sorghum plants. Keywords: Silicate Fertilizer (Si); Manure; Sorghum Plant